Television journalism - Cushion, Stephen (Journalism studies: key texts.)
"Covering issues of ownership, control, policy, and regulation, the book is a blend of theory and history that examines the UK industry from a comparative perspective. It establishes the importance of television journalism, how it converges with other formats, and the ways in which it can survive an ever-changing terrain with the advent of new technologies and new media."--Publisher.